Insentif Pajak dan Sanksi Pajak sebagai Mediasi Pengaruh Kondisi Keuangan Terhadap Kepatuhan Wajib Pajak - Suryanawa, I Ketut; Kresnandra, Anak Agung Ngurah Agung; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 34 No 1 (2024)DO - 10.24843/EJA.2024.v34.i01.p02, 2023)
This research aims to obtain empirical evidence of the influence of financial conditions on taxpayer (WP) compliance, as well as to obtain empirical evidence of the moderation of contingency factors (tax incentives) and contingent factors (tax sanctions) on the influence of financial conditions on taxpayer compliance. Furthermore, it is said that this low tax ratio is, in part, caused by low taxpayer compliance. This research will produce a special taxpayer compliance prediction model in the Covid 19 pandemic era, which is of course very relevant for use by policy makers. The sampling method used in this research used an accidental sampling technique and a sample of 205 respondents was obtained. The research analysis technique uses Moderated Regression analysis. The research results show that financial conditions have a positive effect on individual taxpayer compliance. Tax incentives strengthen the influence of financial conditions on individual taxpayer compliance. Tax sanctions strengthen the influence of financial conditions on individual taxpayer compliance. Keywords: Financial Conditions; Taxpayer Compliance; Tax Incentives; Tax Sanctions